Knowledge, beliefs, and concerns about bone health from a systematic review and metasynthesis of qualitative studies. - Jude des Bordes; Seema Prasad; Greg Pratt; Maria E Suarez-Almazor; Maria A Lopez-Olivo (PLoS ONE)
Background Patients with low bone density or osteoporosis need information for effective prevention or disease management, respectively. However, patients may not be getting enough information from their primary care providers or other sources. Inadequate disease information leaves patients ill-informed and creates misconceptions and unnecessary concerns about the disease. Objective We systematically reviewed and synthesized the available literature to determine patient knowledge, beliefs, and concerns about osteoporosis and identify potential gaps in knowledge. Methods A systematic search was conducted for full-text qualitative studies addressing understanding, literacy, and/or perceptions about osteoporosis and its management, using Medline, EMBASE, Web of Science, Cochrane Library, CINAHL, ERIC, PsychINFO, Psyc Behav Sci Collec, and PubMed, from inception through September 2016. Studies were selected by two reviewers, assessed for quality, and themes extracted using the Joanna Briggs Institute data extraction tool. Thematic analysis was used to identify themes and subthemes. Results Twenty-five studies with a total of 757 participants (including 105 men) were selected for analysis out of 1031 unique citations. Selected studies were from Australia, Canada, Denmark, Norway, the United Kingdom, and the United States. Four main themes emerged: inadequate knowledge, beliefs and misconceptions, concerns about osteoporosis, and lack of information from health care providers. Participants had inadequate knowledge about osteoporosis and were particularly uninformed about risk factors, causes, treatment, and prevention. Areas of concern for participants included diagnosis, medication side effects, and inadequate information from primary care providers. Conclusion Although there was general awareness of osteoporosis, many misconceptions and concerns were evident. Education on bone health needs to reinforce areas of knowledge and address deficits, misconceptions, and concerns.